People's perception of importance of education: a field experience in Dehradun district - Bhoosnurmath, Kashinath
The author has captured people's perception of the importance of education through intense interaction with the villagers, opinion leaders and groups of people in a 5 per cent randomized sample of villages in Dehradun district. Block-wise and hill area versus plain areas analysis resulted in interesting findings. The author concludes that there is a growing awareness among rural population about the importance of education. The time is more ripe now than ever to aim towards hundred per cent literacy in the district by simultaneously taking steps for recruitment, placement and utilization of primary school teachers properly. Reproduced.
Keywords: Dehradun District; Education and State - India - Uttar Pradesh